The performance of non-core property assets held by a state owned enterprise: a case study of Transnet - Munsanje, Abednego Nchimunya (Department of Construction Economics and Management, 2021)
This research looks at Transnet a State owned Enterprise with a key focus on how it manages its non-core property assets that are currently highly dilapidated and in a poor state of repair with resultant sub-optimal returns being derived. The non-core property portfolio of Transnet is immediately visible, by way of comparison, of their deteriorating condition as opposed to those in close proximity or surrounding them that are privately owned. Transnet is a Freight and Logistics state owned company that owns huge tracts of prime and well located land countrywide that are not optimally utilized and also holds a large property portfolio consisting of predominantly 'D' grade buildings that are currently physically, functionally and economically obsolete lacking constant maintenance or engagement in redevelopments. Most assets were initially purpose built to support freight and rail logistics operations but have overtime become functionally obsolete due to changes in logistic chains operations, advancements in technology and nature of goods coming unto the railway system. The current study was aimed at assessing the reasons as to why the non-core property assets are physically deteriorated and achieving below market related returns. The study establishes a framework for optimal management of non-core property assets in Transnet, with literature review establishing the correct approach to issues impacting real estate management such as finance, maintenance and facilities management, property management structure and systems, legislative framework guiding SOE's and corporate governance. Theoretical models have made important contributions to the formalization of certain problems related to management of SOEs and the need to improve corporate governance with a lot of research done in SOEs in China and Europe in general. The key focus of this study was to establish the causes that have resulted in the noncore property assets being highly neglected and in a poor state of repair resulting in sub-optimal returns being achieved on portfolio. The results of the case study within a survey presented a divergent view of core property assets being better managed than non-core property assets. ii The research methodology undertaken was a survey within a case study. The case study is Transnet and the target respondents consisted of personnel involved in the direct management of core and non-core property assets within the company who were interviewed and questionnaires were also used to gather research findings data. The secondary data was analyzed using quarterly asset management data and benchmarked with Investment Property Data (IPD). The research findings present a comprehensive list of challenges faced by Transnet in the management of non-core property assets with the greatest impact being the Public Finance Management Act and National Government Immoveable Assets Management Act which clearly stipulates that when assets no longer serve the core business they must be disposed of. It is also clearly evident that funding cannot be granted for property development projects that are not aligned with the core business of Transnet which is freight and rail logistics. The study brings to the attention that capital investment and strategic decisions related to management of non-core property assets including legislation need to be reviewed. This will greatly shape the future of the non-core property business and its ability to manage its future operations financially viable and sustainable. Alternative sources of funding such as the Real Estate Investment Trusts on the Johannesburg stock exchange are other avenues that can be explored to raise capital funds for upgrading existing property portfolio or raising funds for property developments. The key focus on how the enterprise should behave, and what should be done is to make non-core property assets financially sustainable and viable for the business to achieve desired returns.